Simulation-oriented scenarios: an alternative approach to crisis decision making and emergency management - Rosenthal, Uriel (Contemporary crises, 1990)
This editorial introduction advocates the need to learn from experiences with crisis management in enhancing crisis preparedness and crisis management capabilities. It introduces the concepts of crisis, crisis management, and crisis decision making and goes on to present the method of reconstructive logic as a method of promoting learning about crises. In particular, it stresses the importance of developing alternative scenarios of crisis development and crisis management on the basis of empirical reconstruction of historical cases. Using "what if" methodology may challenge analysts and practitioners alike to achieve a more sophisticated understanding of crisis events and how they may be handled.